2012
DOI: 10.1108/17465661211242813
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and ranking critical success factors of customer experience in banks

Abstract: PurposeThe purpose of this paper is to identify and evaluate the critical success factors which make the dimensions for measuring customer experience (CE) in banking organizations more effective and purposeful. These critical success factors have been prioritized in order to find out which is more important for the five threshold dimensions to achieve favourable CE.Design/methodology/approachThe paper examines the critical success factors of CE which have been identified from the literature survey and through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 78 publications
2
48
0
1
Order By: Relevance
“…Additionally, the center of attention in customer perspective is the experience that they acquire when they utilize products and services (Biswas, 2009). Similarly, in terms of maximizing profitability and brand awareness among customers to enhance loyalty among customers, organizations have to pass the hurdle by providing magnificent experience to customers (Garg, Rahman, Qureshi, & Kumar, 2012;Ismail, 2011). According to a survey by Gurley (2000), it was predicted that customers are filling their online purchasing form but without any purchasing activity, they quit the sequence.…”
Section: Customer Experiencementioning
confidence: 99%
“…Additionally, the center of attention in customer perspective is the experience that they acquire when they utilize products and services (Biswas, 2009). Similarly, in terms of maximizing profitability and brand awareness among customers to enhance loyalty among customers, organizations have to pass the hurdle by providing magnificent experience to customers (Garg, Rahman, Qureshi, & Kumar, 2012;Ismail, 2011). According to a survey by Gurley (2000), it was predicted that customers are filling their online purchasing form but without any purchasing activity, they quit the sequence.…”
Section: Customer Experiencementioning
confidence: 99%
“…Garg et al (2012Garg et al ( , 2014, for instance identified the success criteria and sub-criteria of bank service experience including the affective (customization, core service, online hedonic elements and value addition), sensorial (servicescape and online aesthetics), cognitive (convenience, marketing mix and online functional elements), behavioral (employees, speed, service process), and rational (customer interaction and presence of other customers) aspects. The cognitive factor was the most significant among all the main criteria and convenience factor is the most important among all the sub-criteria in service experience success (Garg et al, 2012(Garg et al, , 2014. Grace and O'cass (2004) also indicated that the core service, employee service, and servicescape make a very significant contribution to the service experience respectively (Grace & O'Cass, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…None of the quality attributes of E-S-QUAL were regarded as attractive attributes. Garg et al (2012) the analytic hierarchy process (AHP) was used in order to evaluate the identified 14 critical factors of CE and to find their priorities for success in banking organizations.…”
Section: Analytic Hierarchy Process (Ahp)mentioning
confidence: 99%